I'm brave! - McMullan, Kate; McMullan , Jim ([Westport, Connecticut] : Balzer + Bray, an imprint of HarperCollinsPublishers, 2015)
He's a big red engine with a siren, a horn, a tank full of water, and whole lotta hose! He's a good-looking' fire truck, and he's brave too. When the alarm sounds, he's gotta drive through smoke and heat straight to a blazing fire!
Ages 4-8.
Keywords: Fire engines -- Juvenile fiction